Al–AlN composite coatings on AZ31 magnesium alloy for surface hardening and corrosion resistance. (June 2021) - Xie, Wenling; Zhao, Yiman; Liao, Bin; Pang, Pan; Wuu, Dongsing; Zhang, Sam
Abstract: Al–AlN composite coatings were prepared using filtered cathodic vacuum arc deposition on AZ31 magnesium alloy substrates. With increasing substrate bias, AlN phase content increased and Al phase content decreased, resulting in increased hardness of the coatings. Transmission electron microscopy morphology of the composite coatings at 100 V bias showed that the metallic Al phase was embedded in the AlN matrix. The coatings significantly enhanced the corrosion resistance of the AZ31 magnesium alloy. The maximum hardness was 512 HV obtained at a bias of 300 V and a minimum corrosion current density was 1.913 × 10 −6 A/cm 2 attained at a bias of 100 V. The effect of substrate bias on microstructure, coating thickness, and residual stress in the coatings was studied in details. Highlights: Al–AlN composite coatings were obtained by a filter cathode vacuum arc deposition. Metallic Al was embedded in the AlN matrix in the Al–AlN composite coatings. Al–AlN composite coatings significantly improved the surface hardness of the AZ31 alloys. Al–AlN composite coatings markedly improved the corrosion resistance of the AZ31 alloys.